Piatoe koleso . Piatoe koleso . The Fifth Wheel . Пятое колесо - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. An exhibition of paintings in the Russian Museum; the writer Tatiana Tolstaia gives a statement on copyright violations of her works. Featured in the program: Tolstaia, Tat'iana Nikitichna (Writer) Выставка картин в Русском музее; заявление писательницы Татьяны Толстой о нарушении ее авторских прав. В программе участвуют: Толстая, Татьяна Никитична (Писательница)